The influence of servicescape elements towards job satisfaction of employees at KSL Resort and Hotel Johor Bahru / Nurul Amalina Md Fauzi - Md Fauzi, Nurul Amalina (Faculty of Business and Management, 2017)
Job satisfaction is very crucial as it effect the employees productivity and organizational’ performance as well. Job satisfaction can be influence by many factors from psychological and physical surroundings of workplace. For this study, it will be focused on servicescape elements or physical environments that employees experience in their workplace. The study aimed at finding the influence of servicescape elements on job satisfaction of employees at KSL Resort and Hotel Johor Bahru. Furthermore, the main objective of this study is to figure out the relationship between ambient conditions, space functionality and, sign and symbol with job satisfaction of employees at KSL Resort and Hotel Johor Bahru. Quantitative method was employed in this study. Questionnaires were distributed to respondents who are employees at KSL Resort and Johor Bahru for data collection. The overall findings of the study indicates that ambient condition and sign and symbol have a relationship with job satisfaction meanwhile space functionality has no relationship with job satisfaction. As a conclusion, some recommendations have been propose for future research in the final part of the project paper.